Targeting EGFR/HER2/HER3 with a Three-in-One Aptamer-siRNA Chimera Confers Superior Activity against HER2+ Breast Cancer - Xiaolin Yu; Sharad Ghamande; Haitao Liu; Lu Xue; Shuhua Zhao; Wenxi Tan; Lijing Zhao; Shou-Ching Tang; Daqing Wu; Hasan Korkaya; Nita J. Maihle; Hong Yan Liu (Elsevier, 2018)
HER family members are interdependent and functionally compensatory. Simultaneously targeting EGFR/HER2/HER3 by antibody combinations has demonstrated superior treatment efficacy over targeting one HER receptor. However, antibody combinations have their limitations, with high immunogenicity and high cost. In this study, we have developed a three-in-one nucleic acid aptamer-small interfering RNA (siRNA) chimera, which targets EGFR/HER2/HER3 in one molecule. This inhibitory molecule was constructed such that a single EGFR siRNA is positioned between the HER2 and HER3 aptamers to create a HER2 aptamer-EGFR siRNA-HER3 aptamer chimera (H2EH3). EGFR siRNA was delivered into HER2-expressing cells by HER2/HER3 aptamer-induced internalization. HER2/HER3 aptamers act as antagonist molecules for blocking HER2 and HER3 signaling pathways and also as tumor-targeting agents for siRNA delivery. H2EH3 enables down-modulation of the expression of all three receptors, thereby triggering cell apoptosis. In breast cancer xenograft models, H2EH3 is able to bind to breast tumors with high specificity and significantly inhibits tumor growth via either systemic or intratumoral administration. Owing to low immunogenicity, ease of production, and high thermostability, H2EH3 is a promising therapeutic to supplement current single HER inhibitors and may act as a treatment for HER2+ breast cancer with intrinsic or acquired resistance to current drugs.